2016
DOI: 10.1039/c6ra13458k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of boron–carbon–nitride as a negative additive for lead acid batteries operating under high-rate partial-state-of-charge conditions

Abstract: For BCN-NAM, under HRPSoC cycling conditions, the dominating elementary process is the formation of PbO instead of PbSO4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In the HRPSoC cycling, the researchers found that BCN-NAM exhibited a gradual reduction in its discharge capacity for a cycling test performed with 22 804 cycles in eight consecutive paths. This experimental analysis shows the productive influence of BCN in LABs . From the given analysis, it is clear that BCN-based materials have prominent applications in lead-based metal-ion batteries, but an in-depth analysis regarding the utilization of their features is necessary to accomplish this.…”
Section: Applications Of Boron Carbon Nitride In Rechargeable Batteriesmentioning
confidence: 83%
“…In the HRPSoC cycling, the researchers found that BCN-NAM exhibited a gradual reduction in its discharge capacity for a cycling test performed with 22 804 cycles in eight consecutive paths. This experimental analysis shows the productive influence of BCN in LABs . From the given analysis, it is clear that BCN-based materials have prominent applications in lead-based metal-ion batteries, but an in-depth analysis regarding the utilization of their features is necessary to accomplish this.…”
Section: Applications Of Boron Carbon Nitride In Rechargeable Batteriesmentioning
confidence: 83%
“…The carbon in NAM increases the electroactive surface area of an electrode, thereby increasing the conductivity of NAM, physically restrict the growth of lead sulfate crystals, and improves the capacitance of the NAM . Apart from carbon, additives like titanium dioxide, bismuth sulfide, boron carbon nitride, were explored by various researchers as a potential NAM additive for LAB …”
Section: Introductionmentioning
confidence: 99%
“…Intensive works have mainly focused on the combination with heteroatoms (N and B) [19][20][21][22] or metal species [23][24][25][26][27][28][29][30][31][32] to elevate the HER overpotential on the carbon materials. 33 For example, Bi 2 O 2 CO 3 /AC has gained considerable attention since its excellent cycling performance and strong interaction as a negative additive for LABs.…”
mentioning
confidence: 99%